Short term inflation forecasting for monetary policy in Nigeria - Mordi, Charles N. O.; Central Bank of Nigeria, Research Department; Adebiyi, Michael A.; Ademgbe, Emmanuel T. (Abuja, Nigeria Central Bank of Nigeria, 2012)
Develops a short term inflation forecasting framework to serve as a tool for analyzing inflation risks in Nigeria.
Includes bibliographical references.
oif 11/05/17
Ref.
Keywords: Inflation; Monetary policy; Nigeria